Role of myeloid-derived suppressor cells in chronic brucellosis - Hou, Shuiping; Kong, Fandong; Li, Xintong; Xu, Yanwen; Chen, Shouyi; Zhang, Sheng; Zhang, Ling; Li, Tingting; Fu, Yongshui; Li, Chengyao; Wang, Wenjing (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Human brucellosis, a Brucella infection caused most common zoonosis in the world, remains a serious public health burden in China. Brucella chronic infection always causes immunosuppressive status and results in severe organ or tissue damages. The aim of this work was to study the role of the myeloid-derived suppressor cells (MDSCs) in human chronic brucellosis. Methods Fifty cases of chronic brucellosis and 40 healthy individual controls were enrolled in this study. We analyzed the frequency and subsets of MDSCs in PBMC between the chronic brucellosis and healthy control groups by flow cytometry. Furthermore, we also measured the inflammatory-related cytokines in serum samples and the MDSCs inhibition ability to the proliferation of T cells in vitro. Results We found that the frequency of MDSCs in peripheral blood and the level of IL-6 and IL-10 Th2 cytokines and Arginase-1 were significantly increased in chronic brucellosis patients. In addition, we also found that the T cell function was suppressed in vitro by co-culturing with MDSCs from brucellosis patients. Conclusion Our study described an increase of immunosuppressive MDSCs in peripheral blood of chronic brucellosis patients. These results contribute to the understanding of Brucella persistent infection, which may provide an insight for effective treatment of chronic brucellosis patients in clinical practice.